(untitled) (International Journal of Engineering and Computer Science, 2018)
This paper will give a new type of laws, which will belong to soft mathematical morphology. These laws correspond to a property called duality in soft mathematical morphology, which is discussed in a new way.. It means this property is thoroughly discussed by the author. It can be said that the laws are also new laws. So it is named by the name of the author.